FT-IR and isotherm study on anion adsorption onto novel chelating fibers - Ko, YG; Choi, US; Kim, TY; Ahn, DJ; Chun, YJ (WILEY-V C H VERLAG GMBH, 2002)
A new chelating fiber, poly(acrylo-amidino diethylenediamine), was synthesized based on polyacrylonitrile fibers in diethylenetriamine with the aid of AlCl3. Complex formation with CrO4 was strongly pH-dependent, as complexes formed only in the presence of NH3+ and NH2+. In the medium pH region, both ionic and hydrogen bonds were formed between poly(acrylo-amidino diethylenediamine) and the chromate ion, as was confirmed by means of FT IR spectroscopy.